Education Technology Industry in Indonesia: EDUKA SYSTEM (PT EDUKA TEKNOLOGI INDONESIA) and The Competition Landscape) (The Indonesian Journal of Business Administration, 2021)
Eduka System is a company engaged in the Education Technology industry. Eduka System provides services like tryout online tests and learning exercises. Starting 2019, based on the decision of the Indonesian government, all prospective students must do a computer-based test as a university entrance exam (UTBK). With this decision, a tryout test service for UTBK emerged so that students get used to taking tests online. Some business people have also begun to see opportunities in this service so many companies have also started providing online tryout services.This research is aimed to help Eduka System to analyze the competitive landsacape of education technology industry in Indonesia. This research uses competitor analysis to compare Eduka System with its competitors. The method used is benchmarking. The results obtained are there are some factors that influence users' loyalty and retention to use Eduka PTN, there are the competitors who held tryouts when Eduka PTN do not, the competitors who have better products, features, and promotions, and the market leader who has other services aside their main services.Keywords: Eduka System, tryout test, competitor analysis, benchmarking